Examining the Influence of Direct and Indirect Taxation on Economic Growth: A Case Study of Pakistan - Munir, Nasir; Ali, Malik Saqib; Nasir, Azra (iRASD Journal of Economics, 2023)
Taxation and expenditure administration represents a significant concern for governments at all levels. Taxation plays a crucial role in the funding and formulation of economic policies. This study undertakes a comparative analysis of Pakistan's direct and indirect taxation systems, their impact on economic progress, and their relationship with inflation. The available data indicate that the impact of indirect taxes on economic growth is more significant compared to that of direct taxes. More precisely, a rise of one percent in indirect taxation results in a corresponding increase of 0.49% in GDP, while direct taxation leads to a GDP increase of 0.22%. Indirect taxes have a greater impact on inflation compared to direct taxes. It is recommended to consider long-term planning, expanding the tax base, reducing tax evasion, and enhancing the efficiency of the tax mix strategy. Indirect taxation has the potential to mitigate wealth inequality and foster economic growth. Tax and monetary policy have the potential to reduce inflation levels.